Clonality assessment of lymphoproliferative lesions using the polymerase chain reaction: An analysis of two methods - Nikhil Moorchung; R B Batra; N S Mani; S S Gill (Wolters Kluwer Medknow Publications, 2011)
Background: Lymphoid malignancies are a heterogeneous group of disorders which may be difficult to differentiate from reactive proliferations even after immunohistochemistry. Polymerase chain reaction (PCR) is believed to be a good adjunct tool for diagnosis. Materials and Methods: We examined 24 cases of neoplastic and non-neoplastic lymphoproliferative lesions in this study and evaluated the PCR as an additional tool in the confirmation of the diagnosis. Two different PCR methodologies were evaluated. Results: In the evaluation of the T-cell PCR, it was seen that the correlation using both the commercial kits and the custom-synthesized primers was highly significant at a P value of <0.05. In the evaluation of the B-cell PCR, it was seen that the correlation using both the commercial kits and the custom-synthesized primers was not significant using either method (P > 0.05). Conclusions: Both the methods showed an excellent concordance for T-cell γ gene rearrangements, However, the same was not seen in the B-cell receptor rearrangements. This may be because of the small sample size or the inability of consensus V primers to recognize complementary DNA sequences in all of the V segments.